Probabilistic thinking and its role in the training of students - S N Dvoryatkina (RUDN Journal of Psychology and Pedagogics, 2010)
In this paper we attempt to reveal the psychological structure and define the shape of probabilistic thinking, the role of probabilistic knowledge in its development. We formulated pedagogical conditions that ensure the productivity of the development of probabilistic thinking.